“When you need it quick, let us ship it right”: on the importance of port efficiency and service quality to comply with food trade standards in Ghana - Lukas Kornher; Daniel Sakyi; Linus Linnaeus Tannor (Review of World Economics, 2024)
Agricultural exports are especially important because of their great potential for poverty reduction among smallholder farmers. However, many African countries, such as Ghana, fail to realize their full export potential due to institutional and technical constraints. This paper examines the importance of port efficiency and service quality in complying with food trade standards in Ghana. We provide a stylized theoretical model in which exporting firms are willing to pay for improved port service quality as long as the marginal revenue derived from a reduced likelihood of (border) rejection exceeds the marginal costs for improved service quality. We test the model's predictions using primary data from 120 agri-food exporters in Ghana. Our results show that about two-thirds of exporting firms have a positive willingness-to-pay for a reduction in the handling time at the port and the risk of spoilage due to inadequate handling. These findings emphasize the importance of trade facilitation measures in improving port efficiency and service quality to accelerate agricultural exports.
Keywords: F13; Q13; Q17; 330; Fruit and vegetable exports; Ghana; Port efficiency; Choice experiment; Food standards; Sanitary and phyto-sanitary regulations